IMF Staff papers : Volume 38 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1991)
The CMEA countries are starting to conduct their trade at world prices and in convertible currencies. These are crucial steps in economic reform but will worsen Eastern Europe's terms of trade and drive it into current account deficit with the U.S.S.R. Proposals have been made for a payments union, resembling the European Payments Union of 1950-58, to ease the transition. Such an arrangement would not function well if it included the U.S.S.R., which would be a persistent creditor. Other ways must be found to deal with the transition.